Investigation of the ejected mass during high-intensity laser solid interaction for improved plasma mirror generation. (4th February 2022) - Indorf, G F H; Scott, G G; Ennen, M A; Forestier-Colleoni, P; Haddock, D; Hawkes, S J; Scaife, L; Bourgeois, N; Symes, D R; Thornton, C; Andreev, A A; Teubner, U; et al.
Abstract: The interaction of very intense and ultrashort laser pulses with solid targets is a topic that has attracted a large amount of interest in science and applications. This interest is boosted by the large progress made in the development of high repetition rate, high-power laser systems. With the significant increase in average power, there is concern about how to deal with ablated debris that may lead to contamination and damage during interaction experiments with solid targets. This issue is also highly relevant in experiments that include plasma mirrors. These are often employed to increase the contrast ratio of the intense laser pulse to unwanted laser pre-pulses from the amplifier chain and/or the background of amplified spontaneous emission. For this reason, the present work investigates the mass ejected from the target into vacuum for different conditions, particularly those present when plasma mirrors are introduced. The total amount of ablated mass can be reduced by making use of a temporally controlled plasma expansion that enhances the plasma mirror reflectivity. In this way, high intensity laser interaction experiments can be carried out with efficient and clean plasma mirrors significantly reducing the degradation of the laser optics and plasma diagnostics placed near the interaction.